1993
DOI: 10.1080/15298669391355134
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Urine Results Used to Assess Chemical Exposure With Emphasis on Creatinine Adjustments: A Review

Abstract: This paper reviews the process of elimination of creatinine (CRE), and the limitations presented when using it to express urine concentrations. This literature review leads to three conclusions: (1) CRE excretion is subject to wide fluctuations due to specific internal and external factors; (2) the use of CRE to correct chemical concentrations in urine will not necessarily improve the correlation to the exposure dose for all chemicals (it may, in fact, worsen the result); and (3) other means of expressing urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
259
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(266 citation statements)
references
References 0 publications
5
259
0
2
Order By: Relevance
“…However, it has been argued due to intra-and interindividual variations in the excretion of creatinine (Boeninger et al, 1993;Hines et al, 2003). In addition, creatinine adjustment for urinary 1-OHP concentration were controversial, since some studies showed little effect of creatinine adjustment on the relationship between airborne pyrene and urinary 1-OHP (Levin et al, 1995;Kuljukka et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been argued due to intra-and interindividual variations in the excretion of creatinine (Boeninger et al, 1993;Hines et al, 2003). In addition, creatinine adjustment for urinary 1-OHP concentration were controversial, since some studies showed little effect of creatinine adjustment on the relationship between airborne pyrene and urinary 1-OHP (Levin et al, 1995;Kuljukka et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Among those, creatinine adjustment has been commonly used to correct urine dilution by dividing 1-OHP concentrations by urinary creatinine concentrations using similar concentration units. Creatinine excretion, however, also varies with many factors such as intake of meat, diurnal variation, age, gender, and other factors (Boeninger et al, 1993;Barr et al, 2005). The creatinine adjustment method, therefore, is still controversial as to whether it actually reduces the measurement variability due to urine dilution.…”
Section: Introductionmentioning
confidence: 99%
“…For MEAA, its concentration in urine and that adjusted for creatinine show statistically similar results for the high, moderate, and low (control) exposure categories. This was not an unexpected result; the use of creatinine to normalize urinary analyte concentrations has been extensively reported to not necessarily improve correlation of dose to exposure for other urinary components (Allessio et al 1985;Boeniger et al 1993;Carrieri et al 2001). Gaines et al (2010) suggested the use of urine specific gravity for biomarker normalization as an alternative to creatinine.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 91%
“…The urinary biomarkers were calculated as uncorrected values and for both specific gravity and creatinine adjusted values. For specific gravity adjustment the average density of 1.016 was used (Boeniger et al 1993). …”
Section: Statisticsmentioning
confidence: 99%